Case report: Para-testicular spindle cell lipoma suspected of well-differentiated liposarcoma - Fujiwara, Kengo; Fujimoto, Kengo; Ibuki, Emi; Ishikawa, Ryo; Hayashida, Yushi (Frontiers in Urology, 2024)
Spindle cell lipoma is a relatively rare benign tumor that can occur in the posterior neck, shoulder, and upper back. Herein, we present a case of intrascrotal spindle cell lipoma in a 71-year-old male who presented with a mass in the left scrotum that had developed over 2 years. Contrast-enhanced computed tomography (CT) revealed a 5.7cm mass accompanying enhanced solid components. Magnetic resonance imaging (MRI) showed a heterogeneous signal intensity. Therefore, a well-differentiated liposarcoma derived from the spermatic cord was suspected; therefore, the patient underwent radical inguinal orchidectomy with high ligation of the spermatic cord. Histopathological examination revealed mature adipocytes and bland-spindle cells. Immunohistochemically, the tumor cells were positive for CD-34 and negative for CDK4, MDM2, and p16. These findings indicated a spindle cell lipoma. Surgical margins were negative. Three months after surgery, no relapse was observed. This case underscores the rarity of para-testicular spindle cell lipoma. While CT and MRI play crucial roles in disease diagnosis, they may not detect all lesions. To prevent overtreatment, it’s essential to also consider pre-surgical examinations and intraoperative findings.